Low temperature dipolar echo in amorphous dielectrics: significance of relaxation and decoherence free two level systems - Burin, Alexander L.; Leveritt III, John M.; Ruyters, Gudrun; Fleischmann, Andreas; Schötz, Christian Dominik; Bazrafshan, Mesoomeh; Faßl, Paul; Schickfus, Manfred; Enss, Christian (epl, 2013)
The nature of dielectric echoes in amorphous solids at low temperatures is investigated. It is shown that at long delay times the echo amplitude is determined by a small subset of two level systems (TLS) having negligible relaxation and decoherence because of their weak coupling to phonons. The echo decay can then be described approximately by power law time dependencies with different powers at times longer and shorter than the typical TLS relaxation time. The theory is applied to recent measurements of two and three pulse dipolar echo in borosilicate glass BK7 and provides a perfect data fit in the broad time and temperature ranges under the assumption that there exist two TLS relaxation mechanisms due to TLS-phonons and TLS-TLS interaction. This interpretation is consistent with the previous experimental and theoretical investigations. Further experiments verifying the theory predictions are suggested.
Gesehen am 12.10.2022